2015
DOI: 10.14738/assrj.21.139
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Factors Affecting Customers’ Purchase Intention: The Mediating Role of Customer Knowledge and Perceived Value

Abstract: Celebrity*endorsers*and*product*packaging*are*two*most*important*factors*in*creating* the* brand* identity* and* help* in* evaluating* a* products* perceived* value* as* well* as* increasing* the* knowledge* about* the* product.* This* study* was* aimed* at* evaluating* the* effect* of* celebrity* endorser* and* product* packaging* on* purchase* intentions* taking* customer*knowledge*and*perceived*value*as*mediating*variables.*The*sample*size*was* 150* respondents* and* the* sample* was* identified* through* n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
3
9
0
2
Order By: Relevance
“…Esse, segundo Johansson (1989), é o motivo de muitas empresas não se mudarem para países com custos de produção mais baixos, pois isso reduz o valor percebido em relação ao produto, impossibilitando a aplicação de preços de venda mais altos. Dessa forma, a informação do país de origem com imagem positiva conferirá vantagem competitiva ao produto, permitindo adoção de preços premium (Johansson & Nebenzahl, 1986), uma vez que o preço de um produto no mercado não está diretamente associado aos seus custos de fabricação, mas ao preço que os consumidores estão dispostos a pagar (Bhakar, Bhakar, & Dubey, 2015).…”
Section: O Efeito País De Origem Do Brasilunclassified
“…Esse, segundo Johansson (1989), é o motivo de muitas empresas não se mudarem para países com custos de produção mais baixos, pois isso reduz o valor percebido em relação ao produto, impossibilitando a aplicação de preços de venda mais altos. Dessa forma, a informação do país de origem com imagem positiva conferirá vantagem competitiva ao produto, permitindo adoção de preços premium (Johansson & Nebenzahl, 1986), uma vez que o preço de um produto no mercado não está diretamente associado aos seus custos de fabricação, mas ao preço que os consumidores estão dispostos a pagar (Bhakar, Bhakar, & Dubey, 2015).…”
Section: O Efeito País De Origem Do Brasilunclassified
“…Purchase intention is defined as consumers" feelings, thoughts, experience and other external factors that they take into account before purchasing a specific product or service [34]. In other words, it represents to what consumers think they may and will buy [35] and the degree to how satisfactory a product or service meets the consumers" demand [36]. Besides, consumer buying behavior can be observed from two different perspectives: (1) what products consumers think about and (2) where consumers tend to buy that item [37].…”
Section: Consumer Purchase Intentionmentioning
confidence: 99%
“…Of all the existing definitions, we concluded that purchase intention is the tendency of the consumer to plan, attempt, or be willing to make a purchase transaction in the future after he evaluates the product or service. Purchase intention can illustrate the consumer's response to buying what the entrepreneur offers (Bhakar, Bhakar, & Dubey, 2015). Purchase intention is known to have a positive relationship with the actual buying behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Purchase intention is known to have a positive relationship with the actual buying behavior. It means that the higher the purchase intention, the higher the actual purchase behavior will occur (Bhakar et al, 2015;Dodds, Monroe, & Grewal, 1991;Schiffman & Kanuk, 2000;Wang, Cheng, & Chu, 2013). Therefore, purchase intention is valued as an important indicator in predicting consumer spending behavior, particularly actual buying behavior (Wu, Yeh, & Hsiao, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation